\(\left(\frac{1}{x-\sqrt{x}}-\frac{1}{\sqrt{x}-1}\right).\frac{x-2\sqrt{x}+1}{\sqrt{x}-1}\)
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

12 tháng 4 2020

\(P=\left(\frac{1}{x-\sqrt{x}}-\frac{1}{\sqrt{x}-1}\right).\frac{x-2\sqrt{x}+1}{\sqrt{x}-1}\)

\(=\left(\frac{1}{\sqrt{x}\left(\sqrt{x}-1\right)}-\frac{1}{\sqrt{x}-1}\right).\frac{\left(\sqrt{x}-1\right)^2}{\sqrt{x}-1}\)

\(=\left(\frac{1}{\sqrt{x}\left(\sqrt{x}-1\right)}-\frac{1}{\sqrt{x}-1}\right).\left(\sqrt{x}-1\right)\)

\(=\frac{1}{\sqrt{x}-1}\)

Để \(P< \sqrt{P}\)

\(\Rightarrow\hept{\begin{cases}P\ge0\\P^2< P\end{cases}}\)

\(\Rightarrow\hept{\begin{cases}P\ge0\\P^2-P< 0\end{cases}}\)

\(\Rightarrow\hept{\begin{cases}P\ge0\\P\left(P-1\right)< 0\end{cases}}\)

\(\Rightarrow\hept{\begin{cases}P\ge0\\0< P< 1\end{cases}}\)

\(\Rightarrow0< P< 1\)

+ ) \(P>0\Rightarrow\frac{1}{\sqrt{x}}-1>0\Rightarrow\frac{1}{\sqrt{x}}>1\)

\(\Rightarrow\sqrt{x}< 1\Rightarrow0< x< 1\)

\(P< 1\Rightarrow\frac{1}{\sqrt{x}-1}< 1\Rightarrow\frac{1}{\sqrt{x}}< 2\)

\(\Rightarrow\sqrt{x}>\frac{1}{2}\Rightarrow x>\frac{1}{4}\)

\(\Rightarrow\frac{1}{4}< x< 1\)

31 tháng 7 2019

#)Giải :

Bài 1 :

a) \(P=\left(\frac{\sqrt{x}-2}{x-1}-\frac{\sqrt{x}+2}{x+2\sqrt{x}+1}\right)\left(\frac{1-x}{\sqrt{2}}\right)^2\)

\(=\left[\frac{\left(\sqrt{x}-2\right)\left(\sqrt{x}+1\right)}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)^2}-\frac{\left(\sqrt{x}+2\right)\left(\sqrt{x}-1\right)}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)^2}\right]\frac{\left(1-x\right)^2}{2}\)

\(=\frac{x-\sqrt{x}-2-x-\sqrt{x}+2}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)^2}.\frac{\left(\sqrt{x}-1\right)^2\left(\sqrt{x+1}\right)^2}{2}\)

\(=\frac{-2\sqrt{x}}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)^2}.\frac{\left(\sqrt{x}-1\right)^2\left(\sqrt{x}+1\right)^2}{2}\)

\(=-\sqrt{x}\left(\sqrt{x}-1\right)\)

b) Để \(P>0\Rightarrow\hept{\begin{cases}\sqrt{x}>0\\1-\sqrt{x}>0\end{cases}\Rightarrow0< x< 1}\)

c) \(P=-x+\sqrt{x}=-\left(x-2\sqrt{x}.\frac{1}{2}+\frac{1}{4}\right)+\frac{1}{4}=-\left(\sqrt{x}-\frac{1}{2}\right)^2+\frac{1}{4}\le\frac{1}{4}\)

Dấu ''='' xảy ra khi \(x=\frac{1}{4}\)

15 tháng 8 2020

ĐKXĐ: x \(\ge\)0; x \(\ne\)1

a) P = \(\left(\frac{2}{\sqrt{x}-1}-\frac{5}{x+\sqrt{x}-2}\right):\left(1+\frac{3-x}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)}\right)\)

P = \(\left(\frac{2\left(\sqrt{x}+2\right)}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)}-\frac{5}{x+2\sqrt{x}-\sqrt{x}-2}\right):\frac{x+\sqrt{x}-2+3-x}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)}\)

P = \(\frac{2\sqrt{x}+4-5}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)}\cdot\frac{\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)}{\sqrt{x}+1}\)

P = \(\frac{2\sqrt{x}+1}{\sqrt{x}+1}\)

b) P = \(\frac{1}{\sqrt{x}}\) <=> \(\frac{2\sqrt{x}+1}{\sqrt{x}+1}=\frac{1}{\sqrt{x}}\)

=> \(\sqrt{x}\left(2\sqrt{x}+1\right)-\sqrt{x}-1=0\)

<=> \(2x+\sqrt{x}-\sqrt{x}-1=0\)

<=> \(x=\frac{1}{2}\)(tm)

c)Với đk: x \(\ge\)0 và x \(\ne\)1

 \(x-2\sqrt{x-1}=0\) (đk: \(x\ge1\))

<=> \(x-1-2\sqrt{x-1}+1=0\)

<=> \(\left(\sqrt{x-1}-1\right)^2=0\)

<=> \(\sqrt{x-1}-1=0\)

<=> \(\sqrt{x-1}=1\)

<=> \(\left(\sqrt{x-1}\right)^2=1\)

<=> \(\left|x-1\right|=1\)

<=> \(\orbr{\begin{cases}x=0\left(ktm\right)\\x=2\left(tm\right)\end{cases}}\)

Với x = 2 => P = \(\frac{2\sqrt{2}+1}{\sqrt{2}+1}=\frac{\left(2\sqrt{2}+1\right)\left(\sqrt{2}-1\right)}{\left(\sqrt{2}-1\right)\left(\sqrt{2}+1\right)}=\frac{4-2\sqrt{2}+\sqrt{2}-1}{2-1}=3-\sqrt{2}\)

15 tháng 8 2020

a) P = \(\frac{2\sqrt{x}-1}{\sqrt{x}+1}\)(sửa lại)

b)  \(\frac{2\sqrt{x}-1}{\sqrt{x}+1}=\frac{1}{\sqrt{x}}\) => \(2x-\sqrt{x}-\sqrt{x}-1=0\)

<=> \(2x-2\sqrt{x}-1=0\)<=> \(2\left(x-\sqrt{x}+\frac{1}{4}\right)-\frac{3}{4}=0\)

<=>  \(2\left(\sqrt{x}-\frac{1}{2}\right)^2=\frac{3}{4}\) <=> \(\left(\sqrt{x}-\frac{1}{2}\right)^2=\frac{3}{8}\)....(tiếp tự lm)

a: \(A=\dfrac{\left(\sqrt{a}-\sqrt{b}\right)^2}{\sqrt{a}-\sqrt{b}}-\dfrac{\sqrt{ab}\left(\sqrt{a}+\sqrt{b}\right)}{\sqrt{ab}}\)

\(=\sqrt{a}-\sqrt{b}-\sqrt{a}-\sqrt{b}=-2\sqrt{b}\)

b: \(B=\dfrac{2\sqrt{x}-x-x-\sqrt{x}-1}{\left(\sqrt{x}-1\right)\left(x+\sqrt{x}+1\right)}\cdot\dfrac{x+\sqrt{x}+1}{x-1}\)

\(=\dfrac{-2x+\sqrt{x}-1}{\sqrt{x}-1}\cdot\dfrac{1}{x-1}\)

c: \(C=\dfrac{x-9-x+3\sqrt{x}}{x-9}:\left(\dfrac{3-\sqrt{x}}{\sqrt{x}-2}+\dfrac{\sqrt{x}-2}{\sqrt{x}+3}+\dfrac{x-9}{x+\sqrt{x}-6}\right)\)

\(=\dfrac{3\left(\sqrt{x}-3\right)}{x-9}:\dfrac{9-x+x-4\sqrt{x}+4+x-9}{\left(\sqrt{x}+3\right)\left(\sqrt{x}-2\right)}\)

\(=\dfrac{3}{\sqrt{x}+3}\cdot\dfrac{\left(\sqrt{x}+3\right)\left(\sqrt{x}-2\right)}{x-4\sqrt{x}+4}\)

\(=\dfrac{3}{\sqrt{x}-2}\)